2022
DOI: 10.3389/fmars.2021.688139
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Population Genomic Analysis and Numerical Simulation to Estimate Larval Dispersal of Acanthaster cf. solaris Between Ogasawara and Other Japanese Regions

Abstract: The estimation of larval dispersal on an ecological timescale is significant for conservation of marine species. In 2018, a semi-population outbreak of crown-of-thorns sea star, Acanthaster cf. solaris, was observed on a relatively isolated oceanic island, Ogasawara. The aim of this study was to assess whether this population outbreak was caused by large-scale larval recruitment (termed secondary outbreak) from the Kuroshio region. We estimated larval dispersal of the coral predator A. cf. solaris between the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…COTS are one of the most extensively studied sea stars and remain an ongoing research priority in many tropical regions [ 22 , 25 , 81 , 119–121 ]. Identifying the key traits and highly adaptive biology of COTS across life stages such as their recently recognised phenotypic plasticity is crucial to understand the outbreak phenomenon.…”
Section: Crown Of Thorns Starfish Will Remain a Concern And Burdenmentioning
confidence: 99%
“…COTS are one of the most extensively studied sea stars and remain an ongoing research priority in many tropical regions [ 22 , 25 , 81 , 119–121 ]. Identifying the key traits and highly adaptive biology of COTS across life stages such as their recently recognised phenotypic plasticity is crucial to understand the outbreak phenomenon.…”
Section: Crown Of Thorns Starfish Will Remain a Concern And Burdenmentioning
confidence: 99%
“…Genetic studies have revealed the transport of larval corals 36 and crown-of-thorn starfish 37 between the Okinawa and Ogasawara Archipelagos, which are more than 1000 km apart, with no large islands in between. Given that corals can be transported long-distances on pumice 1 3 , 5 , 6 , integrating spatiotemporal information on the exact pumice movement on the sea surface with such genetic analyses may help to clarify the dispersal processes of marine organisms in greater detail.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates a potential ability of MAAS methods. MAAS methods have been usually conducted using the Illumina MiSeq platform, in which the read number ranges from 10 4 to 10 5 per sample 17,22,35 . However, our result suggests that there is a room for increasing the number of the genotyped sites if the sequencing throughput increases.…”
Section: Resultsmentioning
confidence: 99%